Polyester resin emulsion for toner, and resin particle and toner using the same
The polyester resin emulsion for toner, with optimized acid value and cation amount ratio, addresses the challenge of forming a uniform and durable shell layer on toner core particles, enhancing adhesion and performance.
Patent Information
- Application Number
- JP2023147781
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-12
- Publication Date
- 2025-03-25
AI Technical Summary
Existing toner technologies face challenges in forming a uniform and defect-free shell layer on toner core particles, which can peel off under development stress in image forming devices, affecting adhesion and performance.
A polyester resin emulsion for toner is developed, where resin particles containing amorphous polyester resin are dispersed in an aqueous medium. The amorphous polyester resin has its carboxyl groups neutralized with a basic substance, and the acid value and cation amount ratio are optimized to ensure proper shell layer formation.
The solution enables the formation of a uniform shell layer on toner core particles that resists peeling under development stress, ensuring excellent adhesion and improved toner performance.
Smart Images

Figure 2025040767000001 
Figure 2025040767000002 
Figure 2025040767000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyester resin emulsion for toner, and to a resin particle and a toner using the same. [Background technology]
[0002] Toners used in electrophotographic image forming apparatuses are required to have better low-temperature fixing properties in response to market demands for energy saving, and at the same time, toners that do not cause so-called blocking, in which toner particles fuse together even in harsh environments of high temperature and humidity, have been developed. In addition, with the increase in the speed of image forming apparatuses, there has been a demand for toners that can fully withstand the stresses imposed on the toner in the developing machine.
[0003] In recent years, development of toners having a so-called core-shell structure, in which a shell layer excellent in heat resistance and mechanical durability is provided on the surface of the toner, has been progressing. Various techniques for forming a core-shell toner have been proposed and put to practical use, and in particular, chemical toners using polyester resins excellent in low-temperature fixing property for both the core particles and the shell particles have become mainstream. For example, Patent Document 1 and Patent Document 2 propose emulsion aggregation toners having a core-shell structure excellent in low-temperature fixing property and mechanical durability.
[0004] In the technique of aggregating shell particles in an emulsion form on the surface of a core particle as in these techniques, it is very important from the viewpoints of low-temperature fixability, heat-resistant storage stability, and mechanical durability to arrange the shell particles uniformly and without defects on the surface of the core particle to form a shell layer. If the shell particles are not formed properly, the shell layer may peel off from the core particle due to development stress in an image forming apparatus, resulting in a significant deterioration in toner performance.
[0005] Meanwhile, Patent Document 3 proposes a technique of blending polyethylene terephthalate (PET) into the resin of the core and shell parts. By introducing polyethylene terephthalate into the shell part, surface exposure of the wax is suppressed and the durability of the toner is improved. Furthermore, the use of recycled polyethylene terephthalate leads to a reduction in the environmental load, such as a reduction in the consumption of petroleum resources. However, when polyethylene terephthalate is introduced into the shell particles that form the shell part, the hydrophobicity of the shell particles decreases, and the cohesiveness of the core particles and shell particles decreases, which makes it difficult to form a uniform shell layer. Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has been made in view of the above background, and has an object to provide a polyester resin emulsion for toner that can form a shell layer by arranging shell particles uniformly and without defects on the surface of a core particle in forming a core-shell structure of a toner, and that can form a shell layer that does not peel off even under development stress in an image forming apparatus and has excellent adhesion to the core particle. [Means for solving the problem]
[0007] As a result of intensive research to solve the above problems, the above problems have been solved as follows: <1> It was found that this problem can be solved by the above configuration. <1> A polyester resin emulsion for toner, comprising resin particles (S) containing at least an amorphous polyester resin (A) dispersed in an aqueous medium, The amorphous polyester resin (A) is a polyester resin obtained by polycondensing an alcohol component and a carboxylic acid component, and a carboxyl group of the polyester resin is neutralized with a basic substance, A polyester resin emulsion for toner, characterized in that, when the acid value of the amorphous polyester resin (A) is A [mgKOH / g] and the amount of cations derived from the basic substance is B [mmol / g], the ratio (B / A) satisfies the following formula (1): 0.89 ≦B / A ≦ 2.23 (1) Effect of the Invention
[0008] According to the present invention, in forming a core-shell structure of a toner, it is possible to provide a polyester resin emulsion for a toner, which can form a shell layer by arranging shell particles uniformly and without defects on the surface of a core particle, and which can form a shell layer that does not peel off even under development stress in an image forming apparatus and has excellent adhesion to the core particle. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] [Polyester resin emulsion for toner] The polyester resin emulsion for toner of the present invention is an emulsion in which resin particles (S) containing an amorphous polyester resin (A) are dispersed in an aqueous medium. The resin particles (S) may contain other resins together with the amorphous polyester resin (A). The aqueous medium may also contain a surfactant, a polymer protective colloid, etc. Hereinafter, the amorphous polyester resin (A) is also referred to as "polyester resin (A)".
[0010] The method for producing the emulsion is not particularly limited, and known dispersion methods can be used, such as a shear emulsification method in which the polyester resin (A) is dissolved in an organic solvent, then added to an aqueous medium, and dispersed by mechanical shear force using a homomixer or homogenizer such as a low-speed shear type, a high-speed shear type, a friction type, a high-pressure jet type, or an ultrasonic type, or a ball mill, a sand mill, or a dyno mill having media, or a phase inversion emulsification method in which the polyester resin is dissolved in an organic solvent, then added to an aqueous medium to invert the phase. In particular, the phase inversion emulsification method is preferably used because it can obtain a homogeneous emulsion with a sharp particle size distribution.
[0011] The particle size of the resin particles (S) in the emulsion in the present invention is not particularly limited, but the median diameter (D50) is preferably 0.05 μm or more and 0.8 μm or less, more preferably 0.1 μm or more and 0.5 μm or less, and particularly preferably 0.15 μm or more and 0.3 μm or more. If the median diameter (D50) is smaller than 0.05 μm, the aggregation efficiency of the shell particles to the core particles decreases, and problems such as insufficient shell layer thickness on the toner surface tend to occur. In addition, if the median diameter (D50) is larger than 0.8 μm, it becomes difficult for the shell particles to aggregate uniformly on the core particle surface, and the shell layer thickness tends to become non-uniform. The median diameter (D50) in the present invention was measured using a laser type particle size distribution measuring device LA-920 (manufactured by Horiba, Ltd.).
[0012] The solid content concentration of the emulsion in the present invention is not particularly limited, but is preferably 5% by mass to 50% by mass, and more preferably 30% by mass to 45% by mass. If it is less than 5% by mass, the aggregation efficiency of the shell particles to the core particles is low, which reduces the productivity of the toner. If it is more than 50% by mass, there is a risk of reducing the dispersion stability of the emulsion. The solid content concentration in the present invention was calculated by drying an emulsion sample weighed on an aluminum cup in a thermostatic chamber set at 150° C. for 3 hours and then weighing the sample again.
[0013] <Phase inversion emulsification method> The phase inversion emulsification method in the present invention includes a method of adding an aqueous medium to a resin solution obtained by dissolving the polyester resin (A) in an organic solvent to perform phase inversion emulsification. In addition, other resins may be dissolved together with the polyester resin (A) and used within a range that does not impair the effects of the invention. Furthermore, a neutralizing agent, a surfactant, a polymer protective colloid, etc. may be added to the resin solution or the aqueous medium as necessary.
[0014] From the viewpoint of dispersion stability, it is preferable to quickly remove the organic solvent from the emulsion consisting of the resin solution and the aqueous medium obtained by the phase inversion emulsification. The method for removing the organic solvent is not particularly limited, and a known desolvation method can be appropriately selected according to the purpose. For example, a method of gradually increasing the temperature of the emulsion while stirring to remove the organic solvent in the system by evaporation; a method of spraying the emulsion into a dry atmosphere such as air or nitrogen while stirring to remove the organic solvent in the system; a method of reducing the pressure while stirring the emulsion to remove the organic solvent in the system by evaporation; and the like can be mentioned. These methods may be carried out alone or in combination.
[0015] - Amorphous polyester resin (A) - The polyester resin (A) in the present invention is a polyester resin obtained by polycondensation of an alcohol component and a carboxylic acid component.
[0016] The alcohol component preferably contains one or more trihydric or tetrahydric alcohols having a linear or branched saturated aliphatic skeleton with a carbon number of 4 to 6. By introducing a trihydric or tetrahydric alcohol having a linear or branched saturated aliphatic skeleton with a carbon number of 4 to 6 into the resin, the hydroxyl value (OHV) of the resin can be controlled and the coagulation property and adhesion to the core particles of the emulsion can be improved.
[0017] Here, the term "straight-chain" in the present invention refers to a structure that has no carbon-carbon bonds other than a carbon chain (hereinafter referred to as "main chain") that connects two oxygen atoms appropriately selected from oxygen atoms derived from hydroxyl groups in the monomer unit of the alcohol component with the minimum number of oxygen atoms, while the term "branched" refers to a structure that has carbon-carbon bonds other than the main chain.
[0018] Examples of the trihydric aliphatic alcohol having 4 to 6 carbon atoms include 1,2,3-butanetriol, 1,2,4-butanetriol, trimethylolethane, 1,2,3-pentanetriol, 1,2,4-pentanetriol, 1,2,5-pentanetriol, 1,3,5-pentanetriol, 2,3,4-pentanetriol, trimethylolpropane, 1,2,3-hexanetriol, 1,2,6-hexanetriol, 1,3,5-hexanetriol, and 2-isopropylpropane-1,2,3-triol.
[0019] Examples of the tetrahydric aliphatic alcohol having 4 to 6 carbon atoms include pentaerythritol, 1,2,3,4-butanetetraol, 1,2,3,4-pentanetetraol, 1,2,3,5-pentanetetraol, 1,2,4,5-pentanetetraol, 1,2,4,5-hexanetetraol, and 1,2,5,6-hexanetetraol. These trihydric or tetrahydric aliphatic alcohols may be used alone or in combination of two or more kinds.
[0020] The content of the trihydric or tetrahydric alcohol having a linear or branched saturated aliphatic skeleton having 4 to 6 carbon atoms is not particularly limited, but is preferably 0.5 mol% to 10 mol%, more preferably 2 mol% to 5 mol% based on the alcohol component in the resin. If it is less than 0.5 mol%, the cohesion to the core particles is not sufficiently obtained, and the number of shell particles that are not shelled tends to increase. If it is more than 10 mol%, the branched chains of the resin become too many, the melt viscosity of the shell part in the toner becomes low, and it becomes difficult to obtain sufficient heat-resistant storage stability and hot offset resistance.
[0021] As the alcohol component, in addition to the trihydric or tetrahydric alcohols having a linear or branched saturated aliphatic skeleton having 4 to 6 carbon atoms, other known alcohols can be used.
[0022] Examples of the other alcohols include aliphatic diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 2,3-butanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 2-ethyl-1,3-hexanediol, 1,8-octanediol, 1,10-decanediol, and 1,12-dodecanediol; diols having an oxyalkylene group such as diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; alicyclic diols such as 1,4-cyclohexanedimethanol, 1,4-sorbitan, and hydrogenated bisphenol A; and alicyclic diols containing ethylene glycol. Examples of the other alcohols include those to which alkylene oxides such as ethylene oxide, propylene oxide, butylene oxide have been added; bisphenols such as bisphenol A, bisphenol F, bisphenol S, etc.; alkylene oxide adducts of bisphenols such as those to which alkylene oxides such as ethylene oxide, propylene oxide, butylene oxide have been added to bisphenols; trihydric or higher aliphatic alcohols such as heptanetriol, octanetriol, decanetriol, sorbitol, dipentaerythritol, etc.; polyphenols such as trisphenol, phenol novolac, cresol novolac, etc.; and alkylene oxide adducts of polyphenols such as those to which alkylene oxides such as ethylene oxide, propylene oxide, butylene oxide have been added to polyphenols. These other alcohols may be used alone or in combination of two or more.
[0023] Among the other alcohols, it is particularly preferable to use 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, and 2,3-butanediol. By using these diols as the alcohol component of the resin, it is possible to form a shell layer that is excellent in balance between low-temperature fixability and mechanical durability. Furthermore, it is more preferable that these diols are derived from biomass, and carbon dioxide emissions can be reduced when the obtained toner is finally incinerated and disposed of.
[0024] The content of 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, and 2,3-butanediol is not particularly limited, but is preferably 30 mol % or more, more preferably 50 mol % or more, and particularly preferably 80 mol % or more, based on the alcohol component in the resin. If it is less than 30 mol %, it is difficult to obtain low-temperature fixability and mechanical durability, and the effect of reducing environmental load is also small.
[0025] Examples of the carboxylic acid component include aliphatic dicarboxylic acids or anhydrides thereof such as succinic acid, adipic acid, sebacic acid, azelaic acid, dodecanedioic acid, maleic acid, citraconic acid, itaconic acid, alkenylsuccinic acid, and fumaric acid; trivalent or higher aliphatic carboxylic acids or anhydrides thereof such as 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxy-2-methyl-2-methylenecarboxypropane, tetra(methylenecarboxy)methane, and 1,2,7,8-octanetetracarboxylic acid; aromatic dicarboxylic acids or anhydrides thereof such as phthalic acid, isophthalic acid, terephthalic acid, and naphthalenedicarboxylic acid; trivalent or higher aromatic carboxylic acids or anhydrides thereof such as trimellitic acid, pyromellitic acid, 1,2,4-benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, 2,5,7-naphthalenetricarboxylic acid, and 1,2,4-naphthalenetricarboxylic acid; and partial lower alkyl esters. These carboxylic acid components may be used alone or in combination of two or more.
[0026] The polyester resin (A) in the present invention may contain a repeating unit derived from so-called polyethylene terephthalate (PET), which is a condensate of terephthalic acid and ethylene glycol, and can be obtained by condensation polymerization while causing an ester exchange reaction together with raw material monomers of the resin. The polyester resin containing the repeating unit derived from PET has excellent mechanical durability and is therefore suitable as a resin for the shell layer of the toner. In addition, it is particularly preferable to use recycled PET as a raw material, which is called recycled PET, because this leads to a reduction in the amount of petroleum resources used and other environmental load reductions.
[0027] On the other hand, when PET is introduced into the shell particles, the hydrophobicity of the shell particles decreases and the cohesiveness between the core particles and the shell particles also decreases, making it difficult to form a uniform shell layer. However, even in the emulsion of the present invention, even if the polyester resin has such PET introduced therein, the cohesiveness and adhesion with the core particles are not impaired.
[0028] The content of the repeating unit derived from the PET is not particularly limited, but is preferably 10% by mass to 70% by mass, more preferably 30% by mass to 60% by mass, based on the components in the resin. If it is less than 10% by mass, it is difficult to obtain the effect of mechanical durability, and if it is more than 70% by mass, it becomes difficult to dissolve in an organic solvent, and further, low-temperature fixability is deteriorated. The condensation polymerization of the alcohol component and the carboxylic acid component can be carried out, for example, in the presence of the esterification catalyst in an inert gas atmosphere at a temperature of 180°C to 250°C.
[0029] The esterification catalyst is not particularly limited, but examples thereof include titanium compounds and tin(II) compounds having no Sn-C bond, and these may be used alone or in combination.
[0030] The titanium compound is preferably a titanium compound having a Ti—O bond, and more preferably a compound having an alkoxy group, an alkenyloxy group or an acyloxy group having a total of 1 to 28 carbon atoms. Examples thereof include titanium diisopropylate bistriethanol aminate, titanium diisopropylate bistriethanol aminate, titanium dipentylate bistriethanol aminate, titanium diethylate bistriethanol aminate, titanium dihydroxyoctylate bistriethanol aminate, titanium distearate bistriethanol aminate, titanium triisopropylate triethanol aminate, titanium monopropylate tris(triethanol aminate), tetra-n-butyl titanate, tetrapropyl titanate, tetrastearyl titanate, tetramyristyl titanate, tetraoctyl titanate, dioctyl dihydroxyoctyl titanate, dimyristyl dioctyl titanate, and the like.
[0031] The amount of the titanium compound present is preferably 0.01 part by mass or more and 1.0 part by mass or less, and more preferably 0.1 part by mass or more and 0.5 part by mass or less, relative to 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. As the tin(II) compound not having an Sn-C bond, a tin(II) compound having an Sn-O bond, a tin(II) compound having an Sn-X (X represents a halogen atom) bond, etc. are preferred, and a tin(II) compound having an Sn-O bond is more preferred. Examples of the tin(II) compound having an Sn-O bond include tin(II) oxalate, tin(II) acetate, tin(II) octanoate, tin(II) 2-ethylhexanoate, tin(II) laurate, tin(II) stearate, tin(II) oleate, and other tin(II) carboxylates having a carboxylic acid group having 2 to 28 carbon atoms; alkoxytin(II) having an alkoxy group having 2 to 28 carbon atoms, such as octyloxytin(II), lauroxytin(II), stearoxytin(II), and oleyloxytin(II); tin(II) oxide; and tin(II) sulfate.
[0032] Examples of the tin(II) compound having an Sn-X (X represents a halogen atom) bond include tin(II) halides such as tin(II) chloride and tin(II) bromide. The amount of the tin(II) compound present is preferably 0.01 part by mass or more and 1.0 part by mass or less, and more preferably 0.1 part by mass or more and 0.5 part by mass or less, relative to 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. When the titanium compound and the tin (II) compound are used in combination, the total amount of the titanium compound and the tin (II) compound is preferably 0.01 parts by mass or more and 1.0 parts by mass or less, and more preferably 0.1 parts by mass or more and 0.5 parts by mass or less, per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component.
[0033] The acid value (AV) is not particularly limited, but is preferably 15 mgKOH / g to 30 mgKOH / g, more preferably 18 mgKOH / g to 25 mgKOH. If the acid value (AV) is less than 15 mgKOH / g, emulsification becomes difficult and the stability of the emulsion tends to deteriorate. If the acid value (AV) is more than 30 mgKOH / g, the charging stability of the toner against environmental changes tends to deteriorate.
[0034] The glass transition temperature of the polyester resin (A) determined from the second DSC curve by differential scanning calorimetry (DSC) is not particularly limited, but is preferably 60° C. to 75° C. If the glass transition temperature is lower than 60° C., the heat-resistant storage stability of the toner deteriorates. If the glass transition temperature exceeds 75° C., the low-temperature fixability tends to deteriorate. The glass transition temperature can be measured using a differential scanning calorimeter (DSC) (for example, Q-200 (manufactured by TA Instruments)).
[0035] The weight average molecular weight (Mw) of the polyester resin (A) measured by gel permeation chromatography (GPC) is not particularly limited, but is preferably 0.8×10 4 ~1×10 5 is preferred, and 1×10 4 ~5×10 4 is more preferable. 4 If it is smaller than 1×10, low temperature fixability is easily obtained, but mechanical durability tends to deteriorate. 5If it is larger, the low temperature fixability tends to deteriorate. The weight average molecular weight (Mw) can be measured using a gel permeation chromatography (GPC) measuring device (for example, HLC-8220GPC (manufactured by Tosoh Corporation)).
[0036] -Other resins- The emulsion of the present invention may contain other resins dissolved together with the polyester resin (A) as long as the effects of the invention are not impaired. The other resins are not particularly limited and can be appropriately selected from known resins according to the purpose. For example, homopolymers of styrene or its substitutes such as polystyrene, poly-p-styrene, and polyvinyltoluene, styrene-p-chlorostyrene copolymers, styrene-propylene copolymers, styrene-vinyltoluene copolymers, styrene-methyl acrylate copolymers, styrene-ethyl acrylate copolymers, styrene-methacrylic acid copolymers, styrene-methyl methacrylate copolymers, styrene-ethyl methacrylate copolymers, styrene-butyl methacrylate copolymers, styrene-α-chloromethyl methacrylate copolymers, styrene-acrylonitrile copolymers, styrene-vinyl methyl ether ... Examples of the resin include styrene-based copolymers such as chirketone copolymers, styrene-butadiene copolymers, styrene-isopropyl copolymers, and styrene-maleic acid ester copolymers, polythiomethyl methacrylate resins, polybutyl methacrylate resins, polyvinyl chloride resins, polyvinyl acetate resins, polyethylene resins, polyester resins, polyurethane resins, epoxy resins, polyvinyl butyral resins, polyacrylic acid resins, rosin resins, modified rosin resins, terpene resins, phenolic resins, aliphatic or aromatic hydrocarbon resins, aromatic petroleum resins, and resins modified to have functional groups capable of reacting with active hydrogen groups such as isocyanate groups. These may be used alone or in combination of two or more.
[0037] - Organic solvents - The organic solvent used in the phase inversion emulsification method of the present invention can be appropriately selected, and examples thereof include ethanol, isopropanol, isobutanol, acetone, methyl ethyl ketone, methyl isobutyl ketone, diethyl ketone, dibutyl ether, tetrahydrofuran, dioxane, methyl acetate, ethyl acetate, isopropyl acetate, toluene, xylene, benzene, carbon tetrachloride, methylene chloride, 1,2-dichloroethane, 1,1,2-trichloroethane, trichloroethylene, chloroform, monochlorobenzene, and dichloroethylidene. These may be used alone or in combination of two or more. Among these, methyl ethyl ketone, ethyl acetate, and isopropyl acetate are particularly preferred from the viewpoints of solvent removability and polyester resin solubility.
[0038] -Aqueous medium- The aqueous medium used in the phase inversion emulsification method of the present invention is not particularly limited and can be appropriately selected depending on the purpose. Examples of the aqueous medium include water and a mixture of water and an organic solvent miscible with water. The amount of the aqueous medium to be added is not particularly limited, but is preferably 80 parts by mass or more and 150 parts by mass or less with respect to 100 parts by mass of the resin solution.
[0039] In the phase inversion emulsification method of the present invention, the rate of addition of the aqueous medium until the resin solution undergoes phase inversion and is completed is not particularly limited, but is preferably 0.1 to 60 parts by mass / min, more preferably 1 to 3 parts by mass / min, relative to 100 parts by mass of the resin solution. If it is less than 0.1 parts by mass / min, the productivity of the toner decreases. If it is more than 60 parts by mass / min, the particle size distribution of the particles becomes broad, which tends to cause variation in the cohesion of the shell particles to the core particles and unevenness of the shell layer.
[0040] -Neutralizer- In the phase inversion emulsification method of the present invention, a neutralizing agent is added to the resin solution or the aqueous medium. The neutralizing agent may be a basic substance, such as ammonia, trimethylamine, ethylamine, diethylamine, triethylamine, diethanolamine, triethanolamine, tributylamine, lithium hydroxide, sodium hydroxide, or potassium hydroxide, and among these, ammonia and sodium hydroxide are preferably used.
[0041] -Surfactants- In the phase inversion emulsification method of the present invention, a surfactant may be added to the resin solution or the aqueous medium, if necessary. The surfactant is not particularly limited and can be appropriately selected depending on the purpose. Examples of the surfactant include anionic surfactants such as alkylbenzenesulfonate, α-olefinsulfonate, and phosphate ester; cationic surfactants of amine salt type such as alkylamine salt, aminoalcohol fatty acid derivative, polyamine fatty acid derivative, and imidazoline, and quaternary ammonium salt type such as alkyltrimethylammonium salt, dialkyldimethylammonium salt, alkyldimethylbenzylammonium salt, pyridinium salt, alkylisoquinolinium salt, and benzethonium chloride; nonionic surfactants such as fatty acid amide derivatives and polyhydric alcohol derivatives; and amphoteric surfactants such as alanine, dodecyldi(aminoethyl)glycine, di(octylaminoethyl)glycine, and N-alkyl-N,N-dimethylammonium betaine.
[0042] -Polymer protective colloid- In the phase inversion emulsification method of the present invention, a polymer protective colloid may be added to the resin solution or the aqueous medium, if necessary. The polymer protective colloid is not particularly limited and may be appropriately selected depending on the purpose. Examples of the polymer protective colloid include acids such as acrylic acid, methacrylic acid, α-cyanoacrylic acid, α-cyanomethacrylic acid, itaconic acid, crotonic acid, fumaric acid, maleic acid, and maleic anhydride; (meth)acrylic monomers containing a hydroxyl group, such as β-hydroxyethyl acrylate, β-hydroxyethyl methacrylate, β-hydroxypropyl acrylate, β-hydroxypropyl methacrylate, γ-hydroxypropyl acrylate, γ-hydroxypropyl methacrylate, 3-chloro-2-hydroxypropyl acrylate, 3-chloro-2-hydroxypropyl methacrylate, diethylene glycol monoacrylate, diethylene glycol monomethacrylate, glycerin monoacrylate, glycerin monomethacrylate, N-methylol acrylamide, and N-methylol methacrylamide; vinyl alcohol; vinyl alcohols such as vinyl methyl ether, vinyl ethyl ether, and vinyl propyl ether; esters of vinyl alcohol and compounds containing a carboxyl group, such as vinyl acetate, vinyl propionate, and vinyl butyrate; acrylamide, methacrylamide, diacetone acrylamide, and methylol compounds thereof; acid chlorides, such as acrylic acid chloride and methacrylic acid chloride; homopolymers or copolymers having a nitrogen atom or a heterocyclic ring thereof, such as vinylpyridine, vinylpyrrolidone, vinylimidazole, and ethyleneimine; polyoxyethylene-based copolymers, such as polyoxyethylene, polyoxypropylene, polyoxyethylene alkylamines, polyoxypropylene alkylamines, polyoxyethylene alkylamides, polyoxypropylene alkylamides, polyoxyethylene nonylphenyl ether, polyoxyethylene lauryl phenyl ether, polyoxyethylene stearyl phenyl ester, and polyoxyethylene nonyl phenyl ester; and celluloses, such as methyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose.
[0043] [Resin particles (T) and toner] The resin particles (T) and toner of the present invention have a core-shell structure obtained by aggregating and fusing shell particles to core particles using at least the polyester resin emulsion of the present invention. After the core-shell structure is formed, the resin particles (T) and toner may be subjected to other processes such as washing, drying, and annealing. Furthermore, the resin fine particles (T) and toner may have an external additive added to their surfaces as necessary.
[0044] The volume average particle diameter (Dv) of the resin particles (T) and the toner is not particularly limited and can be appropriately selected according to the purpose, but in order to obtain a high-quality image with excellent granularity, sharpness, and fine line reproducibility, it is preferably 3 μm to 10 μm, more preferably 4 μm to 7 μm. If the volume average particle diameter (Dv) is less than 3 μm, the image sharpness and fine line reproducibility are excellent, but the fluidity and transferability of the toner may deteriorate. In addition, the ratio (Dv / Dn) of the volume average particle diameter (Dv) to the number average molecular weight (Dn) represents the particle size distribution of the toner, and the closer the value is to 1, the sharper the particle size distribution is. From the viewpoint of sharpness and fine line reproducibility, the Dv / Dn is preferably 1.20 or less, more preferably 1.15 or less. The volume average particle size (Dv) and the number average molecular weight (Dn) can be measured, for example, by using a Coulter Multisizer III (aperture diameter: 100 μm) (manufactured by Beckman Coulter, Inc.).
[0045] The average circularity of the resin particles (T) and the toner is preferably 0.940 to 0.990, and more preferably 0.960 to 0.985, with 15% or less of particles having a circularity of less than 0.94. A substantially spherical toner within the range of the average circularity is effective for forming a high-definition image with excellent transfer efficiency and reproducibility of appropriate density. In addition, a good image with few transfer defects in a fine line image can be obtained. This is considered to be because the toner surface is sufficiently smooth, so that the contact points with the image support are reduced, and the transfer failure of the toner to the transfer material due to moth holes is reduced. A toner having an irregular shape that is smaller than this range and too far from a sphere tends to have poor transferability, and conversely, a toner having a shape larger than this range and close to a sphere has excellent transferability, but in a system employing blade cleaning or the like, cleaning failure occurs on the photoconductor and transfer belt, etc., causing stains on the image. For example, in development or transfer with a low image area ratio, there is little residual toner, and cleaning failure does not cause a particular problem, but in the case of a high image area ratio such as a color photograph image, toner that has not been transferred due to a paper feed failure or the like may remain on the photoconductor as residual toner, and if this accumulates, it will cause background smearing of the image.In addition, it will also contaminate the charging roller that contact-charges the photoconductor, causing a problem that the original charging ability will not be exhibited.
[0046] The average circularity can be measured, for example, using a flow type particle image analyzer FPIA-3000 (manufactured by SYSMEX Co., Ltd.). The average circularity is obtained by calculating the circularity from the two-dimensional image area of each particle captured by a CCD camera, adding up the circularities of each particle, and dividing by the total number of particles. The circularity of each particle can be calculated by dividing the perimeter of a circle having the same projected area as the particle image by the perimeter of the particle projected image.
[0047] <Core-shell structure> The core-shell structure in the present invention refers to a structure in which a shell layer made of a resin is formed on the outermost surface of a core particle to cover the surface of the core particle. By forming such a core-shell structure, the toner has excellent homogeneity, heat-resistant storage stability, and mechanical durability, and is less susceptible to shell peeling due to stress.
[0048] The resin particles (T) having the core-shell structure and the toner are obtained by adding shell particles to a dispersion of core particles dispersed in an aqueous medium, agglomerating the shell resin on the surfaces of the core particles while stirring, and fusing the core particles and the shell particles by heating. Here, a polyester resin emulsion consisting of the resin particles (S) of the present invention is used as the shell particles.
[0049] -Shell layer- The shell layer is obtained by using a polyester resin emulsion consisting of the resin particles (S) of the present invention as shell particles, aggregating the shell particles on the outermost surface of the core particles to form a shell layer, and then heating and fusing the particles. The core particle and the shell layer are preferably in close contact with each other, but are preferably not completely compatible with each other and have a clear region consisting of only the shell layer. In the core-shell structure, the surface of the core particle does not have to be completely covered with the shell layer, but it is preferable that the surface area covered is large from the viewpoints of toner homogeneity, heat-resistant storage stability, and mechanical durability.
[0050] The average thickness of the shell layer is not particularly limited, but is preferably 50 nm to 500 nm, more preferably 100 nm to 200 nm. If the average thickness is less than 50 nm, the protective function of the shell layer for the core particles is reduced, leading to deterioration of heat-resistant storage stability and mechanical durability. If the average thickness is more than 500 nm, low-temperature fixability is impaired.
[0051] The average thickness of the shell layer can be confirmed by cutting a sample in which toner particles are embedded in an epoxy resin or the like with a micromicrotome or an ultramicrotome, and then ultrathinly sliced into slices, using a transmission electron microscope (TEM). In some cases, the ultrathin slices are stained with a staining agent such as ruthenium tetroxide or osmium tetroxide, which makes it easier to visually confirm the core-shell structure. In the present invention, a sample in which toner particles are embedded in an epoxy resin is ultrathinly sliced with an ultramicrotome, and the cross-sectional image is photographed at 20,000 times magnification using a TEM (field emission electron microscope JEM-2100F / manufactured by JEOL), and the photographed image is imported into an image analyzer (LuzexAP / manufactured by Nireco), and the shell layer thickness is measured at five points for each of 30 toner particles, and the average value of the measured values is used to determine the average thickness of the shell layer.
[0052] -Agglutination- When agglomerating shell particles onto the surfaces of core particles by the aggregation method, a resin emulsion that forms the shell particles (hereinafter referred to as "shell resin emulsion") is first dispersed in a dispersion of core particles, and collision energy between particles due to stirring, thermal energy due to heating, and even the addition of an aggregating agent such as an inorganic metal salt, or pH adjustment may be performed. The properties of the shell resin emulsion not only affect the emulsion stability and the cohesiveness with the core particles, but also affect the adhesion with the core particles when the shell particles are heat-fused to form a shell layer.
[0053] In the present invention, it has been found that the property of efficiently and uniformly agglomerating and arranging shell particles on core particles and forming a layer without peeling off shell particles even during heat fusion is excellent when the ratio (B / A) satisfies the following formula (1), where A [mgKOH / g] is the acid value (AV) of the amorphous polyester resin (A) and B [mmol / g] is the amount of cations derived from the basic substance of the carboxyl group neutralized with the basic substance of the amorphous polyester resin (A). 0.89 ≦B / A ≦ 2.23 (1) The value of B is calculated by the following formula, where A [mgKOH / g] is the acid value of the amorphous polyester resin (A). B [mmol / g] =[A[mgKOH / g] / KOH molecular weight (56.11)]×neutralization rate (%)
[0054] If the ratio (B / A) is less than 0.89, the emulsion stability is low and homo-aggregation of the shell resins occurs before they aggregate with the core particles, making it impossible to form a uniform shell layer on the surface of the core particles. If the ratio (B / A) exceeds 2.23, aggregation is promoted by cations derived from basic substances, resulting in the same phenomenon as above. As a result, defects in the shell layer occur, and the number of shell particles that do not aggregate with the core particles increases, remaining in the toner as fine powder and reducing the quality of the toner. In addition, when the shell particles are heat-fused to form the shell layer, the adhesion to the core particles decreases, making the shell layer more likely to peel off, and the shell layer cannot fully function.
[0055] The temperature of the aqueous medium during the aggregation is not particularly limited, but in order to efficiently promote aggregation, it is preferably from 20° C. to about the glass transition temperature (Tg) of the polyester resin (A). The flocculant is not particularly limited, and examples thereof include aluminum chloride, zinc sulfate, magnesium sulfate, aluminum sulfate, potassium aluminum sulfate, sodium chloride, sodium bromide, sodium iodide, sodium fluoride, sodium acetate, sodium acetoacetate, lithium chloride, lithium bromide, lithium iodide, lithium fluoride, lithium acetate, lithium acetoacetate, potassium chloride, potassium bromide, potassium iodide, potassium fluoride, potassium acetoacetate, magnesium bromide, magnesium chloride, magnesium iodide, and magnesium fluoride. , magnesium acetate, magnesium acetoacetate, calcium chloride, calcium bromide, barium bromide, barium chloride, barium iodide, barium fluoride, barium acetate, barium acetoacetate, strontium bromide, strontium chloride, strontium iodide, strontium fluoride, strontium acetate, strontium acetoacetate, zinc bromide, zinc chloride, zinc iodide, zinc fluoride, zinc acetate, zinc acetoacetate, copper bromide, copper chloride, copper iodide, copper fluoride, copper acetate, copper acetoacetate, iron bromide, iron chloride, iron iodide, iron fluoride, iron acetate, or iron acetoacetate. These may be used alone or in combination of two or more.
[0056] The amount of the flocculant to be added is not particularly limited, but is preferably 0.1 to 20 parts by mass, and more preferably 0.5 to 10 parts by mass, relative to 100 parts by mass of the total amount of the core particles and the shell particles. From the viewpoint of uniform flocculation in the reaction system, the flocculant is preferably used as an aqueous solution, and the concentration of the aqueous solution is preferably 1 to 50% by mass, and more preferably 5 to 20% by mass.
[0057] The rate at which the aggregates are added to the aqueous medium is not particularly limited, but is preferably from 0.1 to 5 parts by mass / min, and more preferably from 0.5 to 2 parts by mass / min, relative to 100 parts by mass of the aqueous medium containing the core particles and the shell particles.
[0058] The aggregation can be stopped as necessary. Examples of methods for stopping the aggregation include adding a salt with a low ionic valence, a chelating agent, a surfactant, etc., adjusting the pH, lowering the temperature of the dispersion, and adding a large amount of an aqueous medium to dilute the concentration.
[0059] Examples of the chelating agent include metal salts such as sodium ethylenediaminetetraacetate, sodium gluconate, sodium tartrate, sodium citrate, potassium citrate, and nitrotriacetate salts, and polymer electrolytes.
[0060] -Fusion- The fusion is a step of heating and fusing the aggregated particles consisting of the core particles and the shell particles obtained in the aggregation to form the shell layer, and it is preferable to heat the dispersion of the aggregated particles while stirring. The fusion temperature is not particularly limited, but is preferably equal to or higher than the glass transition temperature (Tg) of the polyester resin (A).
[0061] <Core particle> The core particles are not particularly limited, but may be, for example, particles produced by a kneading and grinding method or a so-called chemical method of granulating particles in an aqueous medium. When using core particles produced by the kneading and grinding method, it is preferable that the core particles are subjected to a spheroidizing treatment and a surface smoothing treatment by a heat treatment or the like in order to form a uniform shell layer.
[0062] The core particles are preferably an aqueous dispersion in order to be aggregated with the polyester resin emulsion of the present invention. Therefore, it is particularly preferable that the core particles are an aqueous dispersion of core particles obtained by a chemical process of granulation in an aqueous medium. In addition, the core particles in the present invention are preferably particles that have not been mixed with an external additive or a flowability improver in order to be used by aggregating shell particles on the surface.
[0063] Examples of the chemical process include a suspension polymerization process, an emulsion polymerization process, a seed polymerization process, a dispersion polymerization process, etc., which are produced using a monomer as a starting material; a dissolution suspension process in which a resin or a resin precursor is dissolved in an organic solvent or the like and dispersed or emulsified in an aqueous medium; a phase inversion emulsification process in which water is added to a solution consisting of a resin or a resin precursor and a suitable emulsifier to invert the phase; and an aggregation process in which resin particles obtained by these processes are aggregated in a dispersed state in an aqueous medium and granulated into particles of a desired size by heating and melting, etc. Among these, the dissolution suspension process and the phase inversion emulsification process, which can easily handle polyester resins having excellent low-temperature fixing properties, and the aggregation process using particles obtained by these processes, are preferred.
[0064] The core particles may be made of any material as long as it satisfies the conditions of the present invention, and may contain, as necessary, a binder resin, a crystalline resin as a fixing aid, a colorant, a release agent, a charge control agent, etc.
[0065] The binder resin is not particularly limited and can be appropriately selected from known resins according to the purpose. For example, homopolymers of styrene or its substitutes such as polystyrene, poly-p-styrene, and polyvinyltoluene, styrene-p-chlorostyrene copolymers, styrene-propylene copolymers, styrene-vinyltoluene copolymers, styrene-methyl acrylate copolymers, styrene-ethyl acrylate copolymers, styrene-methacrylic acid copolymers, styrene-methyl methacrylate copolymers, styrene-ethyl methacrylate copolymers, styrene-butyl methacrylate copolymers, styrene-α-chloromethyl methacrylate copolymers, styrene-acrylonitrile copolymers, styrene-vinyl methyl ether ... Examples of the resin include styrene-based copolymers such as chirketone copolymers, styrene-butadiene copolymers, styrene-isopropyl copolymers, and styrene-maleic acid ester copolymers, polythiomethyl methacrylate resins, polybutyl methacrylate resins, polyvinyl chloride resins, polyvinyl acetate resins, polyethylene resins, polyester resins, polyurethane resins, epoxy resins, polyvinyl butyral resins, polyacrylic acid resins, rosin resins, modified rosin resins, terpene resins, phenolic resins, aliphatic or aromatic hydrocarbon resins, aromatic petroleum resins, and resins modified to have functional groups capable of reacting with active hydrogen groups such as isocyanate groups. These may be used alone or in combination of two or more.
[0066] Among these, it is particularly preferable to use at least one amorphous polyester resin (B), which can improve adhesion to the shell particles in the present invention and obtain a toner with excellent stress resistance. The amorphous polyester resin (B) is not particularly limited, and can be the same as that used in the polyester resin (A).
[0067] The crystalline resin is preferably one that melts at about the fixing temperature. By including such a crystalline resin in the toner, the crystalline resin melts and becomes compatible with the binder resin at the fixing temperature, improving the sharp melting property of the toner and exhibiting an excellent effect of low-temperature fixing property.
[0068] The crystalline resin is not particularly limited as long as it has crystallinity, and can be appropriately selected according to the purpose. Examples include polyester resin, polyurethane resin, polyurea resin, polyamide resin, polyether resin, vinyl resin, modified crystalline resin, etc. These may be used alone or in combination of two or more. Among these, polyester resin (hereinafter referred to as "crystalline polyester resin (C)") is preferable.
[0069] The melting point of the crystalline resin is not particularly limited, but is preferably 60° C. or more and 100° C. or less. If the melting point is less than 60° C., the crystalline resin is likely to start melting at a low temperature, which may reduce the heat-resistant storage stability of the toner. If the melting point is more than 100° C., the effect on low-temperature fixability is not obtained.
[0070] The colorant is not particularly limited, and examples thereof include carbon black, nigrosine dye, iron black, naphthol yellow S, Hansa yellow (10G, 5G, G), cadmium yellow, yellow iron oxide, yellow ocher, yellow lead, titanium yellow, polyazo yellow, oil yellow, Hansa yellow (GR, A, RN, R), pigment yellow L, benzidine yellow (G, GR), permanent yellow (NCG), Balkan fast yellow (5G, R), tartrazine lake, quinoline yellow lake, anthrazan yellow BGL, isoindolinone yellow, red iron oxide, Red lead, vermilion, cadmium red, cadmium mercury red, antimony vermilion, permanent red 4R, para red, physey red, parachlor orthonitroaniline red, lithol fast scarlet G, brilliant fast scarlet, brilliant carmine BS, permanent red (F2R, F4R, FRL, FRLL, F4RH), fast scarlet VD, belkam fast rubin B, brilliant scarlet G, lithol rubin GX, permanent red F5R, brilliant carmine 6B, pigment scarlet 3 B, Bordeaux 5B, Toluidine Maroon, Permanent Bordeaux F2K, Helio Bordeaux BL, Bordeaux 10B, Bon Maroon Light, Bon Maroon Medium, Eosin Lake, Rhodamine Lake B, Rhodamine Lake Y, Alizarin Lake, Thioindigo Red B, Thioindigo Maroon, Oil Red, Quinacridone Red, Pyrazolone Red, Polyazo Red, Chrome Vermilion, Benzidine Orange, Perinone Orange, Oil Orange, Cobalt Blue, Cerulean Blue, Alkaline Blue Lake, Peacock Blue Lake, Victoria Blue - Lake, Metal-free Phthalocyanine Blue, Phthalocyanine Blue, Fast Sky Blue, Indanthrene Blue (RS, BC), Indigo, Ultramarine Blue, Prussian Blue, Anthraquinone Blue, Fast Violet B, Methyl Violet Lake, Cobalt Purple, Manganese Purple, Dioxane Violet, Anthraquinone Violet, Chrome Green, Zinc Green, Chromium Oxide, Pyridian, Emerald Green, Pigment Green B, Naphthol Green B, Green Gold, Acid Green Lake, Malachite Green Lake, Phthalocyanine Green,Examples of the pigments include anthraquinone green, titanium oxide, zinc oxide, and ritbon. These pigments may be used alone or in combination of two or more.
[0071] The content of the colorant in the resin particles (T) or the toner is not particularly limited, but is preferably 1% by mass to 15% by mass, more preferably 3% by mass to 10% by mass. If the content is less than 1% by mass, the coloring power of the toner is reduced, and if it exceeds 15% by mass, poor dispersion of the pigment in the toner may occur, leading to a reduction in the coloring power and a reduction in the electrical properties of the toner.
[0072] The colorant may be used as a master batch composited with a resin. The resin is not particularly limited, and examples thereof include polymers of styrene or its substitutes, styrene-based copolymers, polymethyl methacrylate resins, polybutyl methacrylate resins, polyvinyl chloride resins, polyvinyl acetate resins, polyethylene resins, polypropylene resins, polyester resins, epoxy resins, epoxy polyol resins, polyurethane resins, polyamide resins, polyvinyl butyral resins, polyacrylic acid resins, rosin, modified rosin, terpene resins, aliphatic hydrocarbon resins, alicyclic hydrocarbon resins, aromatic petroleum resins, chlorinated paraffin, and paraffin. These may be used alone or in combination of two or more.
[0073] The release agent is not particularly limited, and examples thereof include carnauba wax, rice wax, montan wax, trimethylolpropane tribehenate, pentaerythritol tetrabehenate, pentaerythritol diacetate dibehenate, glycerin tribehenate, icosanoic acid stearyl, behenic acid esters such as icosyl behenate, behenyl behenate, stearyl behenate, behenyl stearate, and stearyl stearate; polyalkanol esters such as trimellitic acid tristearyl and distearyl maleate; polyalkanoic acid amides such as dibehenylamide; polyalkylamides such as trimellitic acid tristearylamide; dialkyl ketones such as distearyl ketone; polyolefin waxes such as polyethylene wax and polypropylene wax; and waxes such as long-chain hydrocarbons such as paraffin wax, microcrystalline wax, and sazol wax. These may be used alone or in combination of two or more. Among these, alkanoic acid ester waxes are preferably used.
[0074] The melting point of the release agent is not particularly limited, but is preferably from 40° C. to 160° C., more preferably from 50° C. to 120° C., and particularly preferably from 60° C. to 90° C. If the melting point is less than 40° C., the heat-resistant storage stability may be adversely affected, and if it exceeds 160° C., cold offset may easily occur during fixing at low temperatures.
[0075] The content of the release agent in the resin particles (T) or the toner is not particularly limited, but is preferably 1% by mass to 20% by mass, more preferably 3% by mass to 15% by mass, and particularly preferably 3% by mass to 7% by mass. If the content exceeds 20% by mass, the fluidity of the toner may deteriorate.
[0076] The charge control agent is not particularly limited, and examples thereof include nigrosine dyes, triphenylmethane dyes, chromium-containing metal complex dyes, molybdic acid chelate pigments, rhodamine dyes, alkoxy amines, quaternary ammonium salts, alkylamides, phosphorus simple substance or compounds, tungsten simple substance or compounds, fluorine-based activators, metal salts of salicylic acid, and metal salts of salicylic acid derivatives. The content of the charge control agent is not particularly limited, but is preferably 0.1 parts by mass to 10 parts by mass, more preferably 0.2 parts by mass to 5 parts by mass, relative to 100 parts by mass of the resin particles (T) or the toner. If the content exceeds 10 parts by mass, the chargeability of the toner becomes too high, which may lead to a decrease in the fluidity of the developer and a decrease in image density.
[0077] <Cleaning, drying, annealing> The resin particles (T) and toner of the present invention may be subjected to steps such as washing, drying, and annealing, if necessary.
[0078] The washing method is not particularly limited, and examples thereof include centrifugation, reduced pressure filtration, and filter press. Any of the methods can obtain a cake of resin particles (T) and toner, but if washing cannot be performed sufficiently in one operation, the obtained cake may be dispersed again in an aqueous solvent to form a slurry, and the process of extracting toner particles by any of the above methods may be repeated. When washing is performed by reduced pressure filtration or filter press, a washing method may be adopted in which an aqueous solvent is passed through the cake. The aqueous solvent used for the washing may be, for example, water or a mixed solvent obtained by mixing water with an alcohol such as methanol or ethanol. Among these, water is preferred in view of costs and environmental loads due to wastewater treatment. The cake obtained by the washing contains a large amount of the aqueous medium, so it is preferable to dry it.
[0079] The drying method is not particularly limited, and examples thereof include methods using a dryer such as a spray dryer, a vacuum freeze dryer, a reduced pressure dryer, a stationary shelf dryer, a mobile shelf dryer, a fluidized bed dryer, a rotary dryer, or an agitator dryer. The drying is preferably carried out until the moisture content finally becomes less than 1%. The resin particles (T) and toner obtained after drying may be disintegrated using a device such as a jet mill, a Henschel mixer, a super mixer, a coffee mill, an Oster blender, or a food processor to break up aggregates.
[0080] The annealing is preferably carried out particularly when the core particles contain the crystalline polyester resin (C). The annealing is preferably performed at a temperature not lower than the glass transition temperature and not higher than the melting point of the crystalline polyester resin (C), and the annealing is preferably performed for 3 hours to 24 hours, more preferably 6 hours to 15 hours.
[0081] <External additives> Examples of the external additive include inorganic fine particles, polymer fine particles, flowability improvers, and cleaning property improvers.
[0082] -Inorganic fine particles- Examples of the inorganic fine particles include silica, alumina, titanium oxide, barium titanate, magnesium titanate, calcium titanate, strontium titanate, zinc oxide, tin oxide, silica sand, clay, mica, wollastonite, diatomaceous earth, chromium oxide, cerium oxide, red iron oxide, antimony trioxide, magnesium oxide, zirconium oxide, barium sulfate, barium carbonate, calcium carbonate, silicon carbide, and silicon nitride. The primary particle diameter of the inorganic fine particles is preferably 5 nm or more and 2 μm or less, and more preferably 5 nm or more and 500 nm or less. 2 / g or more 500m 2 / g or less is preferable. The content of the inorganic fine particles is preferably from 0.01% by mass to 5% by mass with respect to the total amount of the toner.
[0083] -Polymer-based fine particles- Examples of the polymeric fine particles include polystyrene obtained by soap-free emulsion polymerization, suspension polymerization, or dispersion polymerization, methacrylic acid ester or acrylic acid ester copolymers, silicone, benzoguanamine, nylon, or other polycondensation systems, and polymer particles made of thermosetting resins.
[0084] -Flow improver- The flowability improver is not particularly limited as long as it is capable of performing a surface treatment to increase hydrophobicity and prevent deterioration of flowability and charging properties even under high humidity conditions. Examples of the flowability improver include silane coupling agents, silylation agents, silane coupling agents having a fluorinated alkyl group, organic titanate coupling agents, aluminum coupling agents, silicone oils, and modified silicone oils. It is particularly preferable that the silica and titanium oxide are surface-treated with such a flowability improving agent and used as hydrophobic silica and hydrophobic titanium oxide.
[0085] -Cleaning improver- The cleaning property improver is not particularly limited as long as it is added to the toner in order to remove the developer remaining on the photoconductor or the primary transfer medium after transfer. Examples of the cleaning property improver include fatty acid metal salts such as zinc stearate, calcium stearate, and stearic acid, polymer fine particles produced by soap-free emulsion polymerization such as polymethyl methacrylate fine particles and polystyrene fine particles. The polymer fine particles preferably have a relatively narrow particle size distribution, and the volume average particle size is preferably 0.01 μm to 1 μm.
[0086] -Mixing external additives- The external additive is added to the resin particles (T) and the toner, and is attached to the particle surfaces by a process of mixing them. The mixing method is not particularly limited, and examples of the method include a method of applying an impact force to the mixture with a blade rotating at high speed, a method of introducing the mixture into a high-speed air current, accelerating the mixture, and causing the particles to collide with each other or the composite particles to collide with an appropriate collision plate, etc. Specifically, examples of the mixing means include an Angmill (manufactured by Hosokawa Micron Corporation), a device modified from an I-type mill (manufactured by Japan Pneumatic Co., Ltd.) with reduced grinding air pressure, a Hybridization System (manufactured by Nara Machinery Works, Ltd.), a Cryptron System (manufactured by Kawasaki Heavy Industries, Ltd.), an automatic mortar, etc.
[0087] [Developer] The developer in the present invention contains the toner and further contains other components such as a carrier, which are appropriately selected as necessary. The developer may be a one-component developer or a two-component developer. When the developer is used in a high-speed printer or the like corresponding to the recent improvement in information processing speed, the two-component developer is preferred in terms of improving the life span, etc.
[0088] In the case of the one-component developer using the toner, even if there is a toner balance, i.e., even if toner is supplied to the developer and consumed by development, there is little fluctuation in the particle size of the toner, and there is no toner filming on the developing roller or toner fusion to layer thickness regulating members such as blades for thinning the toner layer, and good and stable developability and images can be obtained even with long-term use (stirring) of the developing means.
[0089] Furthermore, in the case of the two-component developer using the toner, even if the toner is balanced over a long period of time, there is little fluctuation in the toner particle size in the developer, and good and stable developability can be obtained even with long-term stirring in the developing means.
[0090] The carrier is not particularly limited and can be appropriately selected depending on the purpose, but is preferably one having a core material and a resin layer covering the core material.
[0091] The material of the core material is not particularly limited and can be appropriately selected from known materials. For example, manganese-strontium (Mn-Sr)-based materials and manganese-magnesium (Mn-Mg)-based materials of 50 emu / g to 90 emu / g are preferred, and from the viewpoint of ensuring image density, highly magnetized materials such as iron powder (100 emu / g or more) and magnetite (75 emu / g to 120 emu / g) are preferred. In addition, weakly magnetized materials such as copper-zinc (Cu-Zn)-based materials (30 emu / g to 80 emu / g) are preferred, since they can weaken the contact of the toner with the electrostatic latent image carrier in a standing state, which is advantageous for improving image quality. These materials may be used alone or in combination of two or more.
[0092] The particle diameter of the core material is preferably 10 μm or more and 200 μm or less, more preferably 40 μm or more and 100 μm or less, in terms of average particle diameter (weight average particle diameter (D50)). If the average particle diameter (weight average particle diameter (D50)) is less than 10 μm, the distribution of the carrier particles will contain more fine powder, which may reduce the magnetization per particle and cause carrier scattering. If the average particle diameter exceeds 200 μm, the specific surface area will decrease, which may cause toner scattering, and in full color with many solid areas, reproduction of the solid areas may be particularly poor.
[0093] The material of the resin layer is not particularly limited and can be appropriately selected from known resins according to the purpose, and examples thereof include amino resins, polyvinyl resins, polystyrene resins, halogenated olefin resins, polyester resins, polycarbonate resins, polyethylene resins, polyvinyl fluoride resins, polyvinylidene fluoride resins, polytrifluoroethylene resins, polyhexafluoropropylene resins, copolymers of vinylidene fluoride and acrylic monomers, copolymers of vinylidene fluoride and vinyl fluoride, fluoro terpolymers such as terpolymers of tetrafluoroethylene, vinylidene fluoride and non-fluorinated monomers (fluorinated triple (multiple) copolymers), and silicone resins. These may be used alone or in combination of two or more. Among these, silicone resins are particularly preferred.
[0094] The silicone resin is not particularly limited and can be appropriately selected from commonly known silicone resins depending on the purpose. Examples of the silicone resin include straight silicone resins consisting only of organosiloxane bonds; and silicone resins modified with alkyd resins, polyester resins, epoxy resins, acrylic resins, urethane resins, etc. As the silicone resin, commercially available products can be used. Examples of straight silicone resins include KR271, KR255, and KR152 manufactured by Shin-Etsu Chemical Co., Ltd.; and SR2400, SR2406, and SR2410 manufactured by Dow Corning Toray Silicones Co., Ltd.
[0095] The modified silicone resin may be a commercially available product, and examples thereof include KR206 (alkyd-modified), KR5208 (acrylic-modified), ES1001N (epoxy-modified), and KR305 (urethane-modified), manufactured by Shin-Etsu Chemical Co., Ltd.; and SR2115 (epoxy-modified) and SR2110 (alkyd-modified), manufactured by Dow Corning Toray Silicone Co., Ltd. Although the silicone resin can be used alone, it is also possible to use a crosslinking component, a charge amount adjusting component, etc., simultaneously.
[0096] The resin layer may contain conductive powder, etc., as necessary. Examples of the conductive powder include metal powder, carbon black, titanium oxide, tin oxide, and zinc oxide. The average particle size of these conductive powders is preferably 1 μm or less. If the average particle size exceeds 1 μm, it may be difficult to control the electrical resistance.
[0097] The resin layer can be formed, for example, by dissolving the silicone resin or the like in a solvent to prepare a coating solution, uniformly coating the coating solution on the surface of the core material by a known coating method, drying, and then baking. Examples of the coating method include a dipping method, a spraying method, and a brush coating method. The solvent is not particularly limited and can be appropriately selected depending on the purpose. Examples of the solvent include toluene, xylene, methyl ethyl ketone, methyl isobutyl ketone, cellosolve, and butyl acetate.
[0098] The baking method is not particularly limited, and may be an external heating method or an internal heating method. Examples of the method include a method using a fixed electric furnace, a flow type electric furnace, a rotary type electric furnace, a burner furnace, etc., and a method using microwaves.
[0099] The amount of the resin layer in the carrier is preferably 0.01% by mass or more and 5.0% by mass or less. If the amount is less than 0.01% by mass, a uniform resin layer may not be formed on the surface of the core material, and if the amount is more than 5.0% by mass, the resin layer may become too thick, causing granulation of the carrier particles, and uniform carrier particles may not be obtained.
[0100] When the developer is a two-component developer, the content of the carrier in the two-component developer is not particularly limited and can be appropriately selected depending on the purpose. For example, the content is preferably 90% by mass or more and 98% by mass or less, and more preferably 93% by mass or more and 97% by mass or less. The mixing ratio of the toner and carrier in the two-component developer is generally preferably 1 part by mass or more and 10.0 parts by mass or less of the toner per 100 parts by mass of the carrier. EXAMPLES
[0101] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. In the following description, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass".
[0102] (Measurement of glass transition temperature (Tg) of resin and melting point of crystalline resin and wax) The glass transition temperature (Tg) of the resin in the present examples and comparative examples was measured using a differential scanning calorimeter (DSC) Q-200 (manufactured by TA Instruments). 5.0 mg of the resin sample was placed in an aluminum sample pan, which was then placed on a holder unit and set in an electric furnace. 10 mg of alumina was used as a reference, which was placed in an aluminum sample pan in the same way as the sample. In a nitrogen atmosphere, the sample was heated from 0°C to 150°C at a heating rate of 10°C / min (first heating), then cooled from 150°C to 0°C at a heating rate of 10°C / min (cooling down process), and heated again to 150°C at a heating rate of 10°C / min (second heating). The heat absorption and heat generation changes during the above process were measured, and a graph of temperature and heat absorption and generation was drawn to obtain a DSC curve. The obtained DSC curve was analyzed using an analysis program in the Q-200 system. The DSC curve from the second heating run was selected, and the glass transition temperature of the resin sample was determined from the intersection of an extension of the baseline of the DSC curve at a temperature lower than the enthalpy relaxation of the endotherm and a tangent showing the maximum slope in the enthalpy relaxation. Similarly, the DSC curve in the second heating run was selected, and the peak temperature of the endotherm was taken as the melting point of the crystalline resin or wax sample.
[0103] (Measurement of weight average molecular weight (Mw) of resin) The weight average molecular weight (Mw) of the resin in the present examples and comparative examples was measured using a gel permeation chromatography (GPC) measuring device HLC-8220GPC (manufactured by Tosoh Corporation). As the column, a TSKgel SuperHZM-H 15 cm triple column (manufactured by Tosoh Corporation) was used.
[0104] The resin to be measured was dissolved in tetrahydrofuran (THF) (containing a stabilizer, manufactured by Wako Pure Chemical Industries, Ltd.) at 0.15% by mass, filtered through a 0.2 μm filter, and the filtrate was used as a sample. 100 μl of the THF sample solution was injected into the measuring device, and measured at a flow rate of 0.35 mL / min under an environment of 40° C. The molecular weight was calculated using a calibration curve prepared from a monodisperse polystyrene standard sample. As the polystyrene standard sample, Showdex STANDARD series manufactured by Showa Denko Co., Ltd. was used, and THF solutions of the following three types of monodisperse polystyrene standard samples were prepared, and measurements were performed under the above conditions, and a calibration curve was prepared with the retention time of the peak top as the light scattering molecular weight of the monodisperse polystyrene standard sample. An RI (refractive index) detector was used as the detector.
[0105] Solution A: S-7300 2.5mg, S-602 2.5mg, S-46 2.5mg, S-2.8 2.5mg, THF 50mL Solution B: S-3500 2.5mg, S-277 2.5mg, S-18 2.5mg, S-1.3 2.5mg, THF 50mL Solution C: S-1700 2.5mg, S-136 2.5mg, S-6.7 2.5mg, toluene 2.5mg, THF 50mL
[0106] (Measurement of acid value (AV) and hydroxyl value (OHV) of resin) The acid value (AV) and hydroxyl value (OHV) of the resins in the present examples and comparative examples were measured according to the method specified in JIS K0070. However, the acid value was measured using a mixed solvent of acetone, methanol, and toluene (acetone:methanol:toluene=12.5:12.5:75), and the hydroxyl value was measured using tetrahydrofuran (THF).
[0107] (Measurement of the volume average particle size (Dv) of resin particles and toner) The volume average particle size (Dv) of the resin particles and toner in this embodiment and comparative example was measured using a Coulter Multisizer III (aperture diameter 100 μm) (manufactured by Beckman Coulter, Inc.) and analysis software Beckman Coulter Multisizer 3 (version 3.51) (manufactured by Beckman Coulter, Inc.). 10 mg of the measurement sample was added to 5 mL of 10% by mass surfactant (alkylbenzene sulfonate, Neogen SC-A, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), dispersed for 1 minute with an ultrasonic disperser, and then 25 mL of electrolyte Isoton III (manufactured by Beckman Coulter) was added in an arbitrary amount and dispersed for 1 minute with an ultrasonic disperser to prepare a sample dispersion. Next, 100 mL of the electrolyte and an appropriate amount of the sample dispersion were added to a beaker, and 30,000 particles were measured at a concentration where the particle size of 30,000 particles could be measured in 20 seconds, and the volume average particle size (Dv) was calculated from the particle size distribution.
[0108] (Production Example of Amorphous Polyester Resin (A)) -Production of amorphous polyester resins (A-1) to (A-5)- In a reaction vessel equipped with a cooling tube, a stirrer and a nitrogen inlet tube, the raw materials shown in "Raw Material 1" in Table 1 were added so that the molar ratio of hydroxyl group to carboxylic acid (OH / COOH) was 1.2, and 1,000 ppm of tetrabutoxy titanate was added as a condensation catalyst relative to the total monomer amount. The temperature was raised to 200°C over 2 hours under a nitrogen stream, and then the temperature was raised to 230°C over 8 hours, and the reaction was carried out for 5 hours while distilling off the water produced. After that, the reaction was carried out for 1 hour under a reduced pressure of 5mmHg to 15mmHg, and then the reaction was carried out for 1 hour under a reduced pressure of 200°C at normal pressure, and then the reaction was carried out for 1 hour under a reduced pressure of 5mmHg to 20mmHg until the desired molecular weight was reached, to obtain polyester resin (A) [polyester resin (A-1) to (A-5)]. The obtained polyester resins (A-1) to (A-5) were subjected to measurement of the glass transition point (Tg), weight average molecular weight, acid value (AV), and hydroxyl value (OHV).
[0109] (Example 1-1) Manufacture of polyester resin emulsion (EM-1) In a 500 mL separable flask equipped with a stirrer, 150 parts of [polyester resin (A-1)] and 150 parts of methyl ethyl ketone were added, and sodium hydroxide (0.3N) was added in an amount equivalent to a neutralization rate of 75% relative to the acid value of [polyester resin (A-1)] to prepare a resin mixture. Next, while stirring the resin mixture, 400 parts of ion-exchanged water was gradually added to perform phase inversion emulsification. After that, the solvent was removed while reducing the pressure with an evaporator, and ion-exchanged water was added so that the solid concentration was 25%, to obtain [polyester resin emulsion (EM-1)].
[0110] (Example 1-2) Manufacture of polyester resin emulsion (EM-2) In a 500 mL separable flask equipped with a stirrer, 150 parts of [polyester resin (A-1)] and 150 parts of methyl ethyl ketone were added, and sodium hydroxide (0.3N) was added in an amount equivalent to a neutralization rate of 120% relative to the acid value of [polyester resin (A-1)] to prepare a resin mixture. Next, while stirring the resin mixture, 400 parts of ion-exchanged water was gradually added to perform phase inversion emulsification. After that, the solvent was removed under reduced pressure with an evaporator, and ion-exchanged water was added so that the solid concentration was 25%, to obtain [polyester resin emulsion (EM-2)].
[0111] (Examples 1-3 to 1-6) Manufacture of polyester resin emulsions (EM-3) to (EM-6) [Polyester resin emulsion (EM-3)] to [Polyester resin emulsion (EM-6)] were obtained in the same manner as in Example 1, except that [Polyester resins (A-2) to (A-5)] were used instead of [Polyester resin (A-1)] in Example 1.
[0112] (Examples 1 to 7) Manufacture of polyester resin emulsion (EM-7) 3 g of a 1% aqueous solution of sodium hydroxide was added dropwise to the [polyester resin emulsion (EM-4)] to obtain [polyester resin emulsion (EM-7)].
[0113] (Comparative Example 1-1) Manufacture of polyester resin emulsion (EM-8) In a 500 mL separable flask equipped with a stirrer, 150 parts of [polyester resin (A-1)] and 150 parts of methyl ethyl ketone were added, and sodium hydroxide (0.3N) was added in an amount equivalent to a neutralization rate of 40% relative to the acid value of [polyester resin (A-1)] to prepare a resin mixture. Next, while stirring the resin mixture, 400 parts of ion-exchanged water was gradually added to perform phase inversion emulsification. After that, the solvent was removed while reducing the pressure with an evaporator, and ion-exchanged water was added so that the solid concentration was 25%, to obtain [polyester resin emulsion (EM-8)].
[0114] (Comparative Example 1-2) Manufacture of polyester resin emulsion (EM-9) In a 500 mL separable flask equipped with a stirrer, 150 parts of [polyester resin (A-1)] and 150 parts of methyl ethyl ketone were added, and sodium hydroxide (0.3N) was added in an amount equivalent to a neutralization rate of 130% relative to the acid value of [polyester resin (A-1)] to prepare a resin mixture. Next, while stirring the resin mixture, 400 parts of ion-exchanged water was gradually added to perform phase inversion emulsification. After that, the solvent was removed while reducing the pressure with an evaporator, and ion-exchanged water was added so that the solid concentration was 25%, to obtain [polyester resin emulsion (EM-9)].
[0115] (Comparative Example 1-3) Manufacture of polyester resin emulsion (EM-10) In a 500 mL separable flask equipped with a stirrer, 150 parts of [polyester resin (A-3)] and 150 parts of methyl ethyl ketone were added, and sodium hydroxide (0.3N) was added in an amount equivalent to a neutralization rate of 40% relative to the acid value of [polyester resin (A-1)] to prepare a resin mixture. Next, while stirring the resin mixture, 400 parts of ion-exchanged water was gradually added to perform phase inversion emulsification. After that, the solvent was removed while reducing the pressure with an evaporator, and ion-exchanged water was added so that the solid concentration was 25%, to obtain [polyester resin emulsion (EM-10)].
[0116] The median diameter (D50) of each of the polyester resin emulsions (EM-1) to (EM-10) obtained above was measured, and the values are shown in Table 2 together with the neutralization rate (% equivalent), B / A value, and pH.
[0117] In addition, the coagulation properties of the shell particles against coagulating salts were evaluated for [Polyester resin emulsion (EM-1)] to [Polyester resin emulsion (EM-10)]. -Evaluation of the coagulation properties of shell particles against coagulating salts- [Polyester resin emulsion (EM-1)] to [Polyester resin emulsion (EM-10)] were adjusted to a solid content concentration of 10% with ion-exchanged water, and 10 g of the sample liquid was placed in a container. While stirring with a magnetic stirrer, 5% calcium chloride aqueous solution was added dropwise, and the minimum concentration of calcium chloride in the sample liquid when the volume average particle size was more than twice the volume average particle size before the addition of the calcium chloride aqueous solution was defined as the critical aggregation concentration. The volume average particle size was measured with a Nanotrac particle size distribution analyzer (UPA-EX150, Nikkiso Co., Ltd., dynamic light scattering method / laser Doppler method). The "%" values in the evaluation criteria indicate the "critical coagulation concentration." [Evaluation Criteria] ○: 7% or more but less than 12% △: 5% to less than 7% or 12% to less than 14% ×: Less than 5% or more than 14%
[0118] Next, a production example in which the above-obtained [polyester resin emulsion (EM-1)] to [polyester resin emulsion (EM-10)] are used to produce resin particles (T) and toner (TN) will be described.
[0119] (Production Example of Amorphous Polyester Resin (B)) In a reaction vessel equipped with a cooling tube, a stirrer and a nitrogen inlet tube, the acid monomer and alcohol monomer shown in Table 1 were added so that the molar ratio of hydroxyl group to carboxylic acid (OH / COOH) was 1.2, and 1,000 ppm of tetrabutoxy titanate was added as a condensation catalyst relative to the total monomer amount. The temperature was raised to 200°C over 2 hours under a nitrogen stream, and then the temperature was raised to 230°C over 8 hours, and the reaction was carried out for 5 hours while distilling off the water produced. After that, the reaction was carried out for 1 hour under a reduced pressure of 5mmHg to 15mmHg, and then cooled to 200°C. After that, trimellitic anhydride was added in an amount shown in Table 1, and the reaction was carried out at 200°C at normal pressure for 1 hour, and then further reacted under a reduced pressure of 5mmHg to 20mmHg until the desired molecular weight was reached, to obtain an amorphous polyester resin (B). The obtained [amorphous polyester resin (B)] was subjected to measurement of the glass transition point (Tg), weight average molecular weight, acid value (AV), and hydroxyl value (OHV).
[0120] (Production Example of Crystalline Polyester Resin (C)) In a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 1,6-hexanediol, sebacic acid as a dicarboxylic acid component, and 500 ppm of titanium dihydroxybis(triethanolamine) as a condensation catalyst were added to the total monomer amount, and the mixture was heated to 180°C over 2 hours under a nitrogen stream, and reacted for 8 hours while distilling off the water produced. The mixture was then gradually heated to 220°C, and reacted for 5 hours under a nitrogen stream while distilling off the water produced, and then further reduced in pressure from 5mmHg to 20mmHg to obtain [crystalline polyester resin (C)] having a melting point of 68°C, an acid value of 10.5mgKOH / g, and a weight average molecular weight of 11,000.
[0121] (Production Example of Crystalline Polyester Resin Dispersion (D)) In a reaction vessel equipped with a cooling tube, a thermometer and a stirrer, 10 parts by mass of [crystalline polyester resin (C)] and 90 parts by mass of ethyl acetate were placed, heated to 77 ° C. to dissolve thoroughly, and cooled to 30 ° C. over 1 hour while stirring. Then, wet pulverization was performed using an Ultraviscomill (manufactured by Imex) under conditions of a liquid delivery rate of 1.0 kg / hr, a disk peripheral speed of 10 m / sec, a 0.5 mm zirconia bead filling amount of 80 volume %, and 6 passes, and ethyl acetate was added to adjust the solid concentration to 10%, to obtain a [crystalline polyester resin dispersion (D)] having a median diameter (D50) of 0.3 μm measured with a laser particle size distribution measuring device LA-920 (manufactured by Horiba, Ltd.).
[0122] (Example of colorant masterbatch production) -Manufacturing of colorant master batches (MB)- 100 parts by mass of [amorphous polyester resin (B)], 100 parts by mass of cyan pigment (Pigment Blue 15:3), and 50 parts by mass of ion-exchanged water were thoroughly mixed and kneaded in an open roll type kneader (Kneadex / Mitsui Mining Co., Ltd.). The kneading temperature was 80°C, and then the temperature was raised to 120°C to remove water, thereby obtaining [colorant master batch (MB)] with a resin to pigment ratio (mass ratio) of 1:1.
[0123] (Example of wax dispersion production) -Production of wax dispersion (W)- In a reaction vessel equipped with a cooling tube, a thermometer, and a stirrer, 20 parts of ester wax (WE-11, NOF Corp.) with a melting point of 70°C and 80 parts of ethyl acetate were placed, heated to 77°C to dissolve thoroughly, and cooled to 30°C over 1 hour while stirring. Then, using an Ultraviscomill (Aimex), the mixture was wet-pulverized under the conditions of a liquid delivery rate of 1.0 kg / hr, a disk circumferential speed of 10 m / sec, a 0.5 mm zirconia bead filling amount of 80% by volume, and 6 passes, and ethyl acetate was added to adjust the solid concentration to 20%, to obtain a wax dispersion (W) having a median diameter (D50) of 0.6 μm as measured by a laser particle size distribution analyzer LA-920 (Horiba, Ltd.).
[0124] (Example of manufacturing core particle dispersion) - Manufacturing of core particle dispersion (CR) by dissolution suspension method - In a container equipped with a stirrer and thermometer, 68 parts of ion-exchanged water, 1 part of sodium carboxymethylcellulose, 16 parts of a 48% aqueous solution of sodium dodecyl diphenyl ether disulfonate (Eleminol MON-7, manufactured by Sanyo Chemical Industries, Ltd.), and 5 parts of ethyl acetate were mixed and stirred, and 10 parts of a particle size control emulsion consisting of a copolymer of styrene-methacrylic acid-butyl acrylate-ethylene oxide methacrylic acid adduct sulfate sodium salt (solid concentration 20%, median diameter 50 nm, manufactured by Sanyo Chemical Industries, Ltd.) was added to prepare an [aqueous phase solution].
[0125] Next, 76 parts of [amorphous polyester resin (B)], 60 parts of [crystalline polyester resin dispersion (D)], 30 parts of [wax dispersion (W)], and 12 parts of [colorant master batch (MB)] were placed in another container equipped with a stirrer and a thermometer, and ethyl acetate was added so that the solid concentration became 50%, and the mixture was stirred to dissolve thoroughly. Next, the mixture was dispersed at a rotation speed of 8,000 rpm for 2 hours using a TK homomixer (manufactured by Tokushu Kika Co., Ltd.), and the mixture was uniformly dissolved and dispersed to prepare the [oil phase].
[0126] 50 parts of the oil phase was added to the vessel containing the aqueous phase solution, and mixed at a liquid temperature of 30° C. to 40° C. with a TK homomixer (manufactured by Tokushu Kika Co., Ltd.) at 12,000 rpm for 1 minute to obtain an emulsified slurry. The obtained emulsified slurry was transferred to another container equipped with a stirrer, a nitrogen inlet tube, and a thermometer, and the temperature was raised to 50°C while stirring, and ethyl acetate was distilled off under a nitrogen stream. Next, a 10% aqueous sodium hydroxide solution was added to adjust the pH of the emulsified slurry to 12, and the emulsion for particle size control adhering to the particle surfaces in the emulsified slurry was heated in a 45°C environment for 10 hours to dissolve and remove it, and the solid content was obtained by suction filtration. The obtained solids were reslurried in ion-exchanged water in an amount equivalent to 40 times the weight of the solids, and then subjected to a washing process in which the solids were thoroughly stirred and filtered twice. After that, ion-exchanged water was added to the solids again to obtain a core particle dispersion (CR) with a solids concentration adjusted to 25%.
[0127] (Carrier manufacturing example) As the core material, 5,000 parts by mass of Mn ferrite particles (weight average diameter: 35 μm), and as the coating material, 300 parts by mass of toluene, 300 parts by mass of butyl cellosolve, 60 parts of acrylic resin solution (composition ratio methacrylic acid: methyl methacrylate: 2-hydroxyethyl acrylate = 5: 9: 3, solid content 50% toluene solution, Tg 38 ° C.), 15 parts by weight of N-tetramethoxymethylbenzoguanamine resin solution (polymerization degree 1.5, solid content 77% toluene solution) and 15 parts by weight of alumina particles (average primary particle diameter 0.30 μm) were dispersed with a stirrer for 10 minutes to prepare a coating liquid, and the core material and this coating liquid were put into a coating device that forms a swirling flow in a fluidized bed with a rotating bottom plate disk and stirring blades, and the coating liquid was applied onto the core material. The obtained coating material was baked in an electric furnace at 220 ° C. for 2 hours to obtain a [carrier].
[0128] (Example 2-1) -Production of resin particles (T) or toner (TN)- In a container equipped with a stirrer and a thermometer, 320 parts of the core particle dispersion (solid concentration 25%) was put in and stirred, and a 20% aqueous magnesium sulfate solution was dropped at a rate of 2 parts / min so that magnesium sulfate was 1% relative to the total solid content, and then the temperature was raised to 55°C and stirring was performed for 30 minutes. Then, 80 parts of [polyester resin emulsion (EM-1)] (solid concentration 25%) was put in and stirred for 30 minutes, after which 100 parts of a 10% aqueous sodium chloride solution was added, and the temperature was raised to 70°C and stirring was continued until the average circularity became 0.970. Next, the container was transferred to an ice water bath and cooled to room temperature, and suction filtration was performed to obtain a solid content. 800 parts of ion-exchanged water was added to the obtained solid content, and the process of reslurrying by stirring and suction filtration to obtain a solid content was repeated five times, and then dried in a circulating air dryer at 45°C for 48 hours. Then, the mixture was sieved with a 75μm mesh to obtain [resin particles (T-1)], which are resin particles (T). 100 parts of the obtained [resin particles (T-1)] were mixed with 1.0 part of hydrophobic silica (HDK-2000, manufactured by Wacker Chemie) and 0.3 parts of titanium oxide (MT-150AI, manufactured by Teika Co., Ltd.) using a Henschel mixer, and then sieved through a 25 μm mesh to obtain [toner (TN-1)].
[0129] -Manufacture of developer- 100 parts of the carrier and 7 parts of the toner (TN-1) were mixed uniformly for 5 minutes at 48 rpm using a turbulator mixer (manufactured by Willy & Bachofen (WAB)) that rotates the container to mix, to obtain a two-component developer, developer (D-1). This [Developer (D-1)] was used to evaluate the mechanical durability of the toner. The evaluation results are shown in Table 3.
[0130] -Evaluation of the mechanical durability of toner- [Developer (D-1)] was loaded into the development unit of a digital color multifunction printer RICOH IM C5500 (manufactured by Ricoh Co., Ltd.), and the developer was removed after running 30,000 blank prints in monochrome mode. An appropriate amount of the developer was placed in a gauge with a mesh of 32 μm opening, and air was blown to separate the toner and carrier. Next, 10 g of the obtained carrier was placed in a 50 mL glass bottle, 10 mL of methyl ethyl ketone was added, and the bottle was shaken 50 times and left to stand for 10 minutes. After that, the supernatant methyl ethyl ketone solution was placed in a glass cell, and the transmittance of the methyl ethyl ketone solution was measured using a turbidity meter. [Evaluation Criteria] ◎ Transmittance is 95% or more (particularly excellent mechanical durability) ○ Transmittance is 90% or more but less than 95% (excellent mechanical durability) △ Transmittance is between 80% and 89% (mechanical durability is the same as conventional technology) × Transmittance is less than 80% (poor mechanical durability)
[0131] (Examples 2-2 to 2-7 and Comparative Examples 2-1 to 2-3) [Resin particles (T-2)] to [Resin particles (T-10)] and [Toners (TN-2) to (TN-10)] were obtained in the same manner as in Example 2-1, except that [Polyester resin emulsion (EM-2)] to [Polyester resin emulsion (EM-10)] were used instead of [Polyester resin emulsion (EM-1)] in Example 2-1. Next, [toner (TN-2)] to [toner (TN-10)] and [developer (D-2)] to [developer (D-10)] were obtained in the same manner as in Example 2-1, except that [resin particles (T-2)] to [resin particles (T-10)] were used instead of [resin particles (T-1)] in Example 2-1. [Developer (D-2)] to [Developer (D-10)] were used and evaluated in the same manner as in Example 2-1. The evaluation results are shown in Table 3.
[0132] [Table 1]
[0133] [Table 2]
[0134] [Table 3]
[0135] For example, the embodiment of the present invention is as follows. (1) A polyester resin emulsion for a toner, comprising resin particles (S) containing at least an amorphous polyester resin (A) dispersed in an aqueous medium, The amorphous polyester resin (A) is a polyester resin obtained by polycondensing an alcohol component and a carboxylic acid component, and a carboxyl group of the polyester resin is neutralized with a basic substance, A polyester resin emulsion for toner, characterized in that, when the acid value of the amorphous polyester resin (A) is A [mgKOH / g] and the amount of cations derived from the basic substance is B [mmol / g], the ratio (B / A) satisfies the following formula (1): 0.89 ≦ B / A ≦ 2.23 (1) (2) The polyester resin emulsion for toner according to the above (1), wherein the acid value (AV) of the amorphous polyester resin (A) is 15 mgKOH / g or more and 30 mgKOH / g or less. (3) The polyester resin emulsion for toner according to the above (1) or (2), wherein the pH of the polyester resin emulsion for toner is 5.5 or more and 8.0 or less. (4) The polyester resin emulsion for toner according to any one of (1) to (3) above, wherein the alcohol component of the amorphous polyester resin (A) contains one or more trihydric or tetrahydric alcohols having a linear or branched saturated aliphatic skeleton having 4 to 6 carbon atoms. (5) The polyester resin emulsion for toner according to any one of the above (1) to (4), which is a resin emulsion for forming a shell layer used in the production of a toner having a core-shell structure in which a shell layer is provided on the surface of a core particle. (6) The polyester resin emulsion for toner according to the above (5), wherein the core particles contain at least one kind of amorphous polyester resin (B). (7) The polyester resin emulsion for toner according to any one of (1) to (6) above, wherein the alcohol component of the amorphous polyester resin (A) contains at least one selected from the group consisting of 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, and 2,3-butanediol in an amount of 30 mol % or more in the alcohol component. (8) The polyester resin emulsion for toner according to any one of (1) to (7) above, wherein the amorphous polyester resin (A) contains at least a repeating unit derived from polyethylene terephthalate which is a condensate of terephthalic acid and ethylene glycol. (9) Resin particles (T) having a core-shell structure with a shell layer on the surface of a core particle, the shell layer being formed from the polyester resin emulsion for toner according to any one of (1) to (8) above. (10) A toner having a core-shell structure with a shell layer on the surface of a core particle, the shell layer being formed from the polyester resin emulsion for toners according to any one of (1) to (8) above. [Prior art documents] [Patent documents]
[0136] [Patent Document 1] JP 2013-235244 A [Patent Document 2] JP 2010-066651 A [Patent Document 3] Patent No. 6632066
Claims
1. A polyester resin emulsion for toner, comprising resin particles (S) containing at least an amorphous polyester resin (A) dispersed in an aqueous medium, The amorphous polyester resin (A) is a polyester resin obtained by polycondensing an alcohol component and a carboxylic acid component, and a carboxyl group of the polyester resin is neutralized with a basic substance, A polyester resin emulsion for a toner, characterized in that, when the acid value of the amorphous polyester resin (A) is A [mg KOH / g] and the amount of cations derived from the basic substance is B [mmol / g], the ratio (B / A) satisfies the following formula (1): 0.89≦B / A≦2.23...(1)
2. 2. The polyester resin emulsion for toner according to claim 1, wherein the acid value (AV) of the amorphous polyester resin (A) is 15 mgKOH / g or more and 30 mgKOH / g or less.
3. 2. The polyester resin emulsion for toner according to claim 1, wherein the pH of the polyester resin emulsion for toner is 5.5 or more and 8.0 or less.
4. The polyester resin emulsion for toner according to any one of claims 1 to 3, wherein the alcohol component of the amorphous polyester resin (A) contains one or more trihydric or tetrahydric alcohols having a linear or branched saturated aliphatic skeleton having from 4 to 6 carbon atoms.
5. The polyester resin emulsion for toner according to any one of claims 1 to 3, which is a resin emulsion for forming a shell layer used in producing a toner having a core-shell structure in which a shell layer is provided on the surface of a core particle.
6. The polyester resin emulsion for toner according to claim 5 , wherein the core particles contain at least one amorphous polyester resin (B).
7. The polyester resin emulsion for toner according to any one of claims 1 to 3, wherein the alcohol component of the amorphous polyester resin (A) contains at least one selected from the group consisting of 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, and 2,3-butanediol in an amount of 30 mol % or more in the alcohol component.
8. 4. The polyester resin emulsion for toner according to claim 1, wherein the amorphous polyester resin (A) contains at least a repeating unit derived from polyethylene terephthalate which is a condensate of terephthalic acid and ethylene glycol.
9. A resin particle (T) having a core-shell structure with a shell layer on the surface of a core particle, the shell layer being formed from the polyester resin emulsion for toner according to any one of claims 1 to 3.
10. A toner having a core-shell structure with a shell layer on the surface of a core particle, the shell layer being formed from the polyester resin emulsion for toners according to any one of claims 1 to 3.
Citation Information
Patent Citations
Toner, method for manufacturing toner, and electrostatic charge image developer
JP2010066651A
Electrophotographic toner
JP2013235244A
Method for producing toner for developing electrostatic images
JP6632066B2